In vitro effect of a corrosive hostile ocular surface on candidate biomaterials for keratoprosthesis skirt. Issue 9 (16th July 2012) - Tan, Xiao Wei; Riau, Andri; Shi, Zhi Long; Tan, Anna C S; Neoh, Koon Gee; Khor, Khiam Aik; Beuerman, Roger W; Tan, Donald; Mehta, Jodhbir S
Abstract : Aim: Keratoprosthesis (KPro) devices are prone to long-term corrosion and microbiological assault. The authors aimed to compare the inflammatory response and material dissolution properties of two candidate KPro skirt materials, hydroxyapatite (HA) and titania (TiO2 ) in a simulated in vitro cornea inflammation environment. Methods: Lipopolysaccharide-stimulated cytokine secretions were evaluated with human corneal fibroblasts on both HA and TiO2 . Material specimens were subjected to electrochemical and long-term incubation test with artificial tear fluid (ATF) of various acidities. Topography and surface roughness of material discs were analysed by scanning electron microscopy and atomic force microscopy. Results: There were less cytokines secreted from human corneal fibroblasts seeded on TiO2 substrates as compared with HA. TiO2 was more resistant to the corrosion effect caused by acidic ATF in contrast to HA. Moreover, the elemental composition of TiO2 was more stable than HA after long-term incubation with ATF. Conclusions: TiO2 is more resistant to inflammatory degradation and has a higher corrosion resistance as compared with HA, and in this regard may be a suitable material to replace HA as an osteo-odonto-keratoprosthesis skirt. This would reduce resorption rates for KPro surgery.